Bridging The Digital Divide In Indian Smes: The Strategic Role Of Social Media And Digital Marketing In Facilitating ICT Adoption (Journal of Namibian Studies : History Politics Culture, 2023)
This study focuses on the manufacturing industry in Delhi-NCR and investigates how social media and digital marketing tools might encourage ICT adoption among Indian SMEs. According to the study, which uses data from 145 workers in four different organizations, social media use and ICT integration are significantly correlated. Increased market reach, consumer interaction, and operational efficiency are all facilitated by digital tools like email marketing, Google Ads, and SEO. But SMEs also must deal with issues including lack of funding, technical know-how, and change aversion. According to the report, methods for overcoming these obstacles include staff training, utilizing reasonably priced digital solutions, and coordinating digital initiatives with corporate goals. According to the report, SMEs must adopt digital tools to maintain their competitiveness and promote long-term growth in the digital era. Furthermore, it clarifies how SMEs can use these technologies to enhance decision-making, hone tactics, and stimulate creativity to secure long-term success.